Short strenuous training-induced changes in blood coagulation in sportsmen and sportswomen - Paska, T.; Sipos, E.; Tóth, A.; Jeges, S.; Szabados, S.; Kovács, G. L. (Journal of Sports Medicine & Doping Studies, 2018)
Objective: To observe how a short vigorous exercise influences certain coagulation and fibrinolytic parameters in sportsmen and sportswomen. Design: Pre-post parallel-groups. Setting: Heart Centre and Department of Laboratory of Medicine, University Pécs, H-7623, Hungary Participants: A total of 31 healthy individuals (mean age [+SD] 35 + 8 years; 18 males, 13 female), participated in the study at the Heart Centre of the University of Pécs. Participants were active and well-trained active sportsmen (and women) continuously involved in competitive sports activities (basketball, handball or water polo) for at least 10 years. Main Outcome Measures: All participants performed an exercise test on a cycle ergometer. Venous blood samples were obtained for rotational thrombelastometry (ROTEM). Results: In the case of sportsmen significant differences were obtained related to physical exercise in certain nonactivated thrombelastometry (NATEM) measurements. After exercise, the mean clotting time (CT) was shorter (329.3 ± 85.3 vs. 276.7 ± 91.7 seconds, P=0.041) and the maximum clot firmness (MCF) was broader (53.7 ± 4. vs. 60.4 ± 13.7 mm, P=0.034) than before exercise. In sportswomen mean CT was shorter (292.9 ± 65.2 vs. 247.8 ± 105.9 seconds, P=0.04), and the MCF was broader after exercise (59.0 ± 4.1 vs. 65.2 ± 9.7 mm, P=0.04) by NATEM measurements. Conclusions: A tendency for a post-exercise hypercoagulation state following a short-term strenuous exercise has been documented.